Group Analysis of the Generalized Hunter-Saxton System - Bozhkov, Yuri; Junior, Valter Aparecido Silva (Discontinuity, Nonlinearity, and Complexity, 2026)
We find the Lie point symmetries of the generalized two-component Hunter-Saxton system. Then we show that it is nonlinearly self-adjoint and establish the corresponding conservation laws using a recent theorem of Nail Ibragimov which enables one to determine conservation laws for problems without variational structure. Finally we obtain some invariant solutions.